Modern traffic engineering in the system approach to the development of traffic networks : 16th Scientific and Technical Conference "Transport Systems. Theory and Practice 2019" Selected papers /: 16th Scientific and Technical Conference "Transport Systems. Theory and Practice 2019" Selected papers. ([2020]) - Unknown
No abstract available